KETERAMPILAN KERJA ILMIAH SISWA SMA PADA MATERI LAJU REAKSI MENGGUNAKAN MODEL PEMBELAJARAN INKUIRI TERBIMBING - Hartati Widyaningsih, Fransiska Tri; Sahputra, Rachmat; Enawaty, Eny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study was to describe the profile of students's scientific work skills before and after being applied to guided inquiry learning models in the